Pseudoankylosis as a complication of reanimation with neuro-vascular anastomosed gracilis muscle: A case report - Vladimir Machon; Michal Beno; Petr Michl (Advances in Oral and Maxillofacial Surgery)
Pseudoankylosis is an uncommon condition characterized by painless restriction of jaw mobility. It is a pathological condition outside the temporomandibular joint (TMJ) articular structure, with myogenic, osteologic, neurogenic, and psychogenic etiologies. The authors present a case of pseudoankylosis arising as an isolated complication of reanimation with neuro-vascular anastomosed gracilis muscle.